Analytical assessment process of e-learning domain research between 1980 and 2014 - Jalali, S. M. J.; Mahdizadeh, E.; Mahmoudi, M. R.; Moro, S. (International Journal of Management in Education, 2018)
Applying some methods to reduce the time and expenditures of training is inevitable in existing circumstances. Many educational organizations have realized the importance of Electronic Learning (E-learning) and tried to use this approach in leveraging their academic classes. As research in E-learning domain has become one of the most important and interesting subjects, observation in emerging and fading trends of E-learning is a need for the scholars and industry professionals who are interested to study and work in the field. This paper has triggered the investigation and depicting of scientific trends in E-learning by using two scientometric methods named burst detection and clustering analysis. By applying two mentioned methods, the hot topics were identified in the field of E-learning.